Synthesis of γ-lactone and δ-lactone analogues of Atranone F via radical cyclisation approach - Mohd Fauzi, Nawwar Fathiah (2013)
Radical cyclisation is a method have been reported to successfully cyclise either C=C (alkene) or alkyne (C≡C) in the attempt of making heterocyclic compounds. New approach has been done in this research where nitrile group (C≡N) proved to cyclise the desired lactones. Atranone F which is a natural product that was isolated from toxigenic fungus named Stachybotrys chartarum was chosen for the synthesis of lactones analogues in this research. Atranone F contains both 5-membered ring (γ) and 6-membered ring (δ) lactones which have many applications in medicines and agricultures. Analogue structures of both γ- and δ-lactones were prepared from their corresponding cyanohydrins via 2 steps of reactions; 1) acylation and 2) radical cyclisation. For the acylation reaction, three α-cyanobromoesters; 1-cyanoethyl 2-bromopropanoate (75e), 1-cyanocyclohexyl 2-bromopropanoate (75f) and 1-cyanoethyl 2-bromoethanoate (75g) together with four β-cyanobromoesters; 1-cyanopropan-2-yl 2-bromopropanoate (77e), 1-cyano-2-methylpropan-2-yl 2-bromopropanoate (77f), 1-cyanopropan-2-yl 2-bromoethanoate (77g) and 1-cyano-2-methylpropan-2-yl 2-bromoethanoate (77h) have been successfully synthesized. In total, five new esters have been produced including (75f), (75g), (77e), (77f) and (77g). All esters products were cyclised to lactones using radical chemistry under the treatment with tris(trimethylsilyl)silane (TTMSH) and azobisisobutyronitrile (AIBN) in toluene. Three analogue structures of γ-lactone; 4-amino-3,5-dimethylfuran-2-one (78e), 4-amino-5-cyclohexyl-3-methyl-3-ene-2-one (78f, new compound) and 4-imino-5-methylfuran-2-one (78g, new compound) were obtained. Meanwhile, four analogue of δ-lactone have been synthesized (all new compounds); 4-imino-5-hydro-3,6-dimethylpyran-2-one (79e), 4-amino-5-hydro-3,6,6-trimethylpyran-2-one (79f), 4-imino-3,5-dihydro-6-methylpyran-2-one (79g) and 4-imino-3,5-dihydro-6,6-dimethylpyran-2-one (79h). Two types of biological activities have been carried out on the cyanobromoesters and the lactones produced in order to determine their activities; 1) Ichthyotoxic test and 2) Cytotoxic assays. Esters 75e, 75f, 75g and 77g showed strong ichthyotoxic activity with TLM values of 6.26, 4.00, 2.85 and 4.00 ppm respectively. For the cytotoxic test, esters 75f, 75g, 77e, 77g, 77h and lactone 79h showed good to moderate activity against HL60 cell lines (% viability: 7.1-40.1).